Numerical Heat Transfer and Fluid Flow 2021 - Bartosik, Artur (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint focuses on experiments, modellings, and simulations of heat transfer and fluid flow. Flowing media comprise single- or two-phase fluids that can be both compressible and incompressible. The reprint presents unique experiments and solutions to problems of scientific and industrial relevance in the transportation of natural resources, technical devices, industrial processes, etc. In the presented works, the formulated physical and mathematical models together with their boundary and initial conditions and numerical computation methods for constitutive equations lead to solutions for selected examples in engineering.